The Ammonite Tirolites idrianus – A Paleontological Icon of the Idrija UNESCO Global Geopark (Slovenia) - Mojca Gorjup Kavčič; Matija Križnar (Geoconservation Research)
Idrija UNECO Global Geopark embraces the area of Idrija Municipality in the western part of Slovenia, with an area of 294 km2. Its main town Idrija, with a famous mercury ore deposit beneath, has always been a home to several European naturalists, who explored natural features, plants, animals and fossils of the area since the beginning of mining in 1490. The ammonite Tirolites idrianus is one of the most important fossils finds in the area of the Idrija Geopark. It is named after Idrija and is an index fossil. This review focuses on the ammonite Tirolites idrianus, its type locality and stratigraphic distribution in the area of the Idrija Geopark. We also discuss means of interpreting the value and importance of this fossil to various groups of visitors, such as school groups, and groups of visitors in the Visitor Centre.